Sistem Pendukung Keputusan dengan Metode Simple Additive Weighting (SAW) Untuk Evaluasi Karyawan di PT. SJAL Silaut - Suryana, Febriyanno; ., Kusdianto (LPPM Universitas Dharma Andalas, 2026)
The use of information technology to support work activities has become an essential requirement to achieve effective and efficient performance. Human limitations in processing highly complex data are a key reason why technology has become a primary alternative solution. This study aims to develop a web-based Decision Support System (DSS) to assist in the evaluation of the best employees at PT SJAL. Previously, the evaluation process was conducted manually, which often led to issues such as subjectivity in assessment, time inefficiency, and suboptimal data management. The proposed system is designed to provide a more objective, accurate, and efficient solution by applying the Simple Additive Weighting (SAW) method. The SAW method was selected due to its ability to handle multi-criteria decision-making in a simple and effective manner through weighted summation of each alternative based on predetermined criteria. The criteria used in this study include discipline, work quality, attendance, teamwork, and initiative. The system implementation was developed using the PHP programming language and a MySQL database. The development stages consist of literature review, data collection, requirements analysis, system design using UML, implementation, and system testing. The results indicate that the system is capable of accelerating the evaluation process, improving accuracy, and generating more objective and measurable employee evaluation recommendations. Therefore, the application of the SAW method is expected to serve as an effective decision support tool for the management of PT SJAL in determining the best employees.